Prognostic Value of Systemic Immune-inflammatory Index in Pulmonary Embolism - Mehmet Mermer; İlker Kaçer; Ahmet Çağlar (Global Emergency and Critical Care)
Objective: This study aimed to investigate the extent to which the systemic immune-inflammatory index (SII) is associated with patients with acute pulmonary embolism (PE), compare the SII with other commonly used biomarkers and scoring systems, and evaluate its suitability for routine use in PE risk classification. Materials and Methods: Patients with acute PE admitted in 2021 were retrospectively reviewed. A cut-off value for the SII was obtained to examine the predictive value of the SII for 30-day mortality as the primary outcome. The secondary outcome of the study was to compare the SII with other predictors of 30-day mortality in patients with acute PE. Results: A total of 139 patients with a mean age of 68.33±14.58 years were included in the study. The cut-off value for 30-day mortality was an SII of ≥0.904 (sensitivity: 88.5%; specificity: 58.4%; area under the curve: 0.803; p<0.001). Lactate, age, right ventricular dysfunction (RVD), and SII ≥0.904 were independent risk factors for 30-day mortality in PE (p<0.05). The SII has a strong correlation with lactate and the presence of RVD (p<0.001). Conclusion: The SII was found to be strongly associated with RVD, age, and lactate in patients with acute PE. Prospective studies may prove that the SII can fill the gap of inexpensive, rapid, and accessible prognostic biomarkers in rural emergency departments where echocardiography is not accessible.